Psychological stress, adverse life events and breast cancer incidence: a cohort investigation in 106, 000 women in the United Kingdom. Issue 1 (December 2016) - Schoemaker, Minouk; Jones, Michael; Wright, Lauren; Griffin, James; McFadden, Emily; Ashworth, Alan; Swerdlow, Anthony
Abstract Background Women diagnosed with breast cancer frequently attribute their cancer to psychological stress, but scientific evidence is inconclusive. We investigated whether experienced frequency of stress and adverse life events affect subsequent breast cancer risk. Methods Breast cancer incidence was analysed with respect to stress variables collected at enrolment in a prospective cohort study of 106, 000 women in the United Kingdom, with 1783 incident breast cancer cases. Relative risks (RR) were obtained as hazard ratios using Cox proportional hazards models. Results There was no association of breast cancer risk overall with experienced frequency of stress. Risk was reduced for death of a close relative during the 5 years preceding study entry (RR = 0.87, 95 % confidence interval (CI): 0.78–0.97), but not for death of a spouse/partner or close friend, personal illness/injury, or divorce/separation. There was a positive association of divorce with oestrogen-receptor-negative (RR = 1.54, 95 % CI: 1.01–2.34), but not with oestrogen-receptor-positive breast cancer. Risk was raised in women who were under age 20 at the death of their mother (RR = 1.31, 95 % CI: 1.02–1.67), but not of their father, and the effect was attenuated after excluding mothers with breast or ovarian cancer (RR = 1.17, 95 % CI: 0.85–1.61). Conclusions This large prospective study did not show consistent evidence for an association of breast cancer risk with perceived stress levels or adverse life events in the preceding 5 years, or loss of parents during childhood and adolescence.